Kedudukan Pengemudi Ojek Sebagai Mitra Kerja Dalam Perjanjian Pengangkutan Berbasis Aplikasi - Laisina, Steven; Kuahaty, Sarah Selfina; Lakburlawal, Mahrita Aprilya (Faculty of Law Universitas Pattimura, 2025)
Application-based public transportation is a concept where public transportation services such as taxis, car sharing, or other public transportation are integrated and operated using application technology, especially mobile applications. Application-based public transportation is an innovation that brings many benefits to the community, both in terms of ease of access to transportation, increased security, and cost efficiency. The Partnership Agreement between the driver and the application company is referred to as a partnership agreement. The responsibility of the driver is adjusted to the losses of the consumer, Article 234 paragraph (1) of Law Number 22 of 2009 concerning Traffic and Road Transportation states that